Dynamics of Adrenal Steroids Are Related to Variations in Th1 and Treg Populations during Mycobacterium tuberculosis Infection in HIV Positive Persons - Quiroga, María Florencia (2012)
Tuberculosis (TB) remains the most frequent cause of illness and death from an infectious agent, and its interaction with HIV has devastating effects. We determined plasma levels of dehydroepiandrosterone (DHEA), its circulating form DHEA-suphate and cortisol in different stages of M. tuberculosis infection, and explored their role on the Th1 and Treg populations during different scenarios of HIV-TB coinfection, including the immune reconstitution inflammatory syndrome (IRIS), a condition related to antiretroviral treatment. DHEA levels were diminished in HIV-TB and HIV-TB IRIS patients compared to healthy donors (HD), HIV+ individuals and HIV+ individuals with latent TB (HIV+LTB), whereas dehydroepiandrosterone sulfate (DHEA-s) levels were markedly diminished in HIV-TB IRIS individuals. HIV-TB and IRIS patients presented a cortisol/DHEA ratio significantly higher than HIV+, HIV-LTB and HD individuals. A positive correlation was observed between DHEA-s and CD4 count among HIV-TB individuals. Inversely, cortisol plasma level inversely correlated with CD4 count within HIV-TB individuals. M. tuberculosis-specific Th1 lymphocyte count was increased after culturing PBMC from HIV-TB individuals in presence of DHEA. We observed an inverse correlation between DHEA-s plasma level and Treg frequency in co-infected individuals, and CD4+FoxP3+ Treg frequency was increased in HIV-TB and IRIS patients compared to other groups. Strikingly, we observed a prominent CD4+CD25-FoxP3+ population across HIV-TB and HIV-TB IRIS patients, which frequency correlated with DHEA plasma level. Finally, DHEA treatment negatively regulated FoxP3 expression without altering Treg frequency in co-infected patients. These data suggest an enhancer role for DHEA in the immune response against M. tuberculosis during HIV-TB coinfection and IRIS.